Developing STEM-Based Digital Worksheet to Encourage Students' Problem-Solving Skills - Susanti, Ely; Aisyah, Nyimas; Silaen, Elza Oktaviani (Universitas PGRI Palembang, 2025)
Mathematics education in the 21st century, a field increasingly shaped by rapid technological advancement and global demands for critical thinking, necessitates the use of contextual, technology-enhanced learning media that promote higher-order thinking skills, particularly in the area of problem solving. Addressing this need, the present study focused on developing a STEM-based digital worksheet, a technology-integrated instructional tool aimed at enhancing students’ mathematical problem-solving skills within the topic of the Pythagorean Theorem. Adopting a Research and Development (R&D) framework, specifically the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study involved a series of methodical phases designed to ensure both pedagogical soundness and technological relevance. Data collection involved conducting interviews and observations, analyzing relevant documents, validating content through expert review, and administering both practicality questionnaires and performance-based assessments grounded in Polya’s problem-solving rubric. Validation by three subject-matter experts, serving as evaluators of content quality and instructional alignment, resulted in an average score of 83.68%, denoting high validity. Practicality, assessed through one-on-one and small-group trials, achieved a mean score of 82.33%, reflecting strong user acceptance and ease of implementation. A field test with 30 students revealed an average problem-solving score of 75%, with notable strengths in identifying and understanding the problem, and relative weaknesses in the final stage of reviewing solutions. These findings, while preliminary, suggest that developing and implementing STEM-based digital worksheets can serve as a promising approach to fostering mathematical problem solving by embedding learning in contextual, interactive, and technologically enriched environments.